Plutonium, 137Cs and uranium isotopes in Mongolian surface soils. (January 2017) - Hirose, K.; Kikawada, Y.; Igarashi, Y.; Fujiwara, H.; Jugder, D.; Matsumoto, Y.; Oi, T.; Nomura, M.
Abstract: Plutonium ( 238 Pu and 239, 240 Pu), 137 Cs and plutonium activity ratios ( 238 Pu/ 239, 240 Pu) as did uranium isotope ratio ( 235 U/ 238 U) were measured in surface soil samples collected in southeast Mongolia. The 239, 240 Pu and 137 Cs concentrations in Mongolian surface soils (<53 μm of particle size) ranged from 0.42 ± 0.03 to 3.53 ± 0.09 mBq g −1 and from 11.6 ± 0.7 to 102 ± 1 mBq g −1, respectively. The 238 Pu/ 239, 240 Pu activity ratios in the surface soils (0.013–0.06) coincided with that of global fallout. The 235 U/ 238 U atom ratios in the surface soil show the natural one. There was a good correlation between the 239, 240 Pu and 137 Cs concentrations in the surface soils. We introduce the migration depth to have better understanding of migration behaviors of anthropogenic radionuclides in surface soil. We found a difference of the migration behavior between 239, 240 Pu and 137 Cs from 137 Cs/ 239, 240 Pu – 137 Cs plots for the Mongolian and Tsukuba surface soils; plutonium in surface soil is migrated easier than 137 Cs. Highlights: This is a first report of plutonium concentrations in Mongolian surface soils. The plutonium activity concentrations in the Mongolian surface soils ranged from 0.42 ± 0.03 to 3.53 ± 0.09 mBq g −1 . 238 Pu/ 239, 240 Pu and 137 Cs/ 239, 240 Pu activity ratios reveal that plutonium in the Mongolian surface soils originated from global fallout. Plutonium moves easier than 137 Cs in soil column according to chemical migration processes.